Quality of life of women with untreated vulval lichen sclerosus assessed with vulval quality of life index (VQLI). (28th January 2021) - Wijaya, Marlene; Lee, Geoffrey; Fischer, Gayle
Abstract: Background/Objective: The diagnosis of vulval lichen sclerosus (VLS) is often delayed, and little is known about quality of life (QoL) of women with it prior to receiving diagnosis and treatment. This study aimed to investigate the impact on QoL on patients with previously untreated VLS using the Vulval Quality of Life Index (VQLI). Methods: A prospective cross‐sectional survey of patients attending a dermato‐gynaecology practice in Sydney, Australia from March 2018 to November 2019. Patients with a new biopsy‐proven diagnosis of VLS not previously commenced on topical corticosteroid treatment were invited to complete the VQLI. Results: A total of 68 participants with median age of 58 (interquartile range, IQR 48–67) years. Median symptom duration was 24 (IQR 11–60) months. Scarring was present in 53% of participants. The median total score was 13.5 (IQR 7.5–22.0), global score 1.0 (IQR 1.0–2.0). Twelve per cent had nil to minimal effect on QoL, 38% had a mild effect on QoL, 28% had a moderate effect on QoL, 22% had a severe effect on QoL, and none had a very severe effect on QoL. The highest‐scoring domains were symptoms, followed by sexuality, anxiety and activities of daily living. Conclusion: There was significant impairment in all QoL areas of women with untreated VLS. Most experienced moderate‐to‐severe impairment as a result of the disease and approximately half had already developed scarring at the time of diagnosis. The findings emphasise the importance of improved awareness, early diagnosis and early commencement of treatment in VLS.